2021
DOI: 10.3390/f12081000
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm Study on Allelopathic Effects of Leaf Litter Leachates and Purified Condensed Tannins from Kandelia obovata on Germination and Growth of Aegiceras corniculatum

Abstract: Kandelia obovata (Ko) and Aegiceras corniculatum (Ac) are common and dominant plant species in mangrove wetlands in South China, which are distributed in similar tidal zones along the coastline. The present study aimed to determine the allelopathic effects of leaf litter leachates (LLLs) from Ko and their purified condensed tannins (PCTs) on the germination and growth of Ac by mangrove microcosms. Replicate pots containing five different levels of LLLs and PCTs were separately prepared and propagules of Ac wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Similarly, Chen and Peng [ 30 ] showed that leaf aqueous extracts of A. marina and B. gymnorhiza inhibited the growth of cabbage (a model species) and K. candel (species following A. marina in mangrove succession). In addition, Lang et al [ 63 ] demonstrated the allelopathic potential of K. obovata against one of its associated species A. corniculatum in a Chinese mangrove, indicating that allelopathy plays a role in mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chen and Peng [ 30 ] showed that leaf aqueous extracts of A. marina and B. gymnorhiza inhibited the growth of cabbage (a model species) and K. candel (species following A. marina in mangrove succession). In addition, Lang et al [ 63 ] demonstrated the allelopathic potential of K. obovata against one of its associated species A. corniculatum in a Chinese mangrove, indicating that allelopathy plays a role in mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…On the positive side, litter protects seeds from herbivores (Hu et al, 2016; Nakhoul et al, 2020), enables seed germination by controlling soil temperature fluctuations (Xia et al, 2015), alleviates seed desiccation by shielding the soil surface from ultraviolet light (Visscher et al, 2016) and promotes seed vigour by creating water diffusion barriers for dry grasslands and microclimates for shady forests (Chen, Ma, et al, 2018; Ruprecht et al, 2010). Conversely, litter input can also make certain constraints stronger, such as negatively impacting seeds by placing them in deep shade or darkness (Rotundo & Aguiar, 2005), or by releasing allelochemicals from coniferous (Kainulainen et al, 2003) and broadleaved litter (Lang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, litter input can also make certain constraints stronger, such as negatively impacting seeds by placing them in deep shade or darkness (Rotundo & Aguiar, 2005), or by releasing allelochemicals from coniferous (Kainulainen et al, 2003) and broadleaved litter (Lang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kandelia obovata is not only a dominant mangrove species along the south-eastern coast of China but also an important species for mangrove afforestation [35]. As a pioneer species, K. obovata is mainly distributed at low tide and middle tide zones, where it is frequently subjected to upwelling [36,37]. K. obovata can survive in areas with salinity of up to 27.58‰ [38].…”
Section: Introductionmentioning
confidence: 99%